A gene regulatory network anchored by LIM homeobox 1 for embryonic head development. Issue 9 (14th September 2018) - Sibbritt, Tennille; Ip, Chi K.; Khoo, Poh‐Lynn; Wilkie, Emilie; Jones, Vanessa; Sun, Jane Q. J.; Shen, Joanne X.; Peng, Guangdun; Han, Jing‐Dong J.; Jing, Naihe; Osteil, Pierre; Ramialison, Mirana; et al.
Summary: Development of the embryonic head is driven by the activity of gene regulatory networks of transcription factors. LHX1 is a homeobox transcription factor that plays an essential role in the formation of the embryonic head. The loss of LHX1 function results in anterior truncation of the embryo caused by the disruption of morphogenetic movement of tissue precursors and the dysregulation of WNT signaling activity. Profiling the gene expression pattern in the Lhx1 mutant embryo revealed that tissues in anterior germ layers acquire posterior tissue characteristics, suggesting LHX1 activity is required for the allocation and patterning of head precursor tissues. Here, we used LHX1 as an entry point to delineate its transcriptional targets and interactors and construct a LHX1‐anchored gene regulatory network. Using a gain‐of‐function approach, we identified genes that immediately respond to Lhx1 activation. Meta‐analysis of the datasets of LHX1‐responsive genes and genes expressed in the anterior tissues of mouse embryos at head‐fold stage, in conjunction with published Xenopus embryonic LHX1 (Xlim1) ChIP‐seq data, has pinpointed the putative transcriptional targets of LHX1 and an array of genetic determinants functioning together in the formation of the mouse embryonic head.